Respuesta :

Answer:

True

Step-by-step explanation:

(x + 4)² = (x + 4) (x + 4)

x² + 4² = x² + 16

Hello.

No, (x+4)² doesn't equal x²+16.

Let's see why.

Remember that

x times x = x²

4 times 4 = 4²=16

So it seems like (x+4)² is equal to x²+16.

However,

(x+4)²≠x²+16.

Well, what IS that equal to?

Turns out that

(x+4)² is equal to x² + twice the product of x and 4 +16 (!)

(x+4)²=x²+2*4*x+4²

(x+4)²=x²+8x+16

Therefore, (x+4)²=x²+8x+16.

I hope it helps.

Have an outstanding day. :)

[tex]\boxed{imperturbability}[/tex]